Heart Rate Recovery 10 Seconds After Cessation of Exercise Predicts Death. Issue 8 (11 September 0207) - van de Vegte, Yordi J.; van der Harst, Pim; Verweij, Niek
Abstract : Background: Heart rate recovery (HRR) is commonly defined as the decrease of heart rate at 1 minute after cessation of exercise and is an important predictor of all‐cause mortality and death associated with coronary artery disease. However, HRR at earlier time intervals after cessation has not been well evaluated and might better reflect PNS reactivation. We hypothesize that early HRR indices within the first minute is better associated with all‐cause and coronary artery disease mortality compared with HRR at 1 minute. Methods and Results: The prognostic value of HRR at 10, 20, 30, 40, and 50 seconds after cessation of exercise was investigated in 40 727 selected UK Biobank participants (mean age 56 years, 45% male) free from cardiovascular disease. During a median follow‐up period of 6 years, 536 participants died (including 39 of coronary artery disease). In multivariable analyses, including adjustments for aerobic exercise capacity, cardiovascular risk factors, and factors associated with mortality in general, only HRR at 10 seconds remained predictive of both all‐cause and coronary artery disease mortality. Effects of HRR were larger and more significant when measured early after exercise cessation. Moreover, the association of change in heart rate between 10 seconds and 1 minute after exercise cessation with mortality was dependent on HRR at 10 seconds. Conclusions: We provide evidence that decreased HRR at 10 seconds after cessation of exercise is a superior predictor of outcome compared with HRR at later time intervals. This observation might have important implications for the future reporting and interpretation of exercise tests.